NH4+-K+ co-loaded clinoptilolite as a binary fertilizer. Issue 1 (2nd January 2020) - Eslami, Mahboubeh; Khorassani, Reza; Fotovat, Amir; Halajnia, Akram
ABSTRACT: Understanding the potential of clinoptilolite (CLI) for adsorption of NH4 + and K +, providing appropriate fertilizer formula, and evaluation of the produced zeolitic nutrient sources (ZNSs) to meet the plant need are the main objectives of this study. Three ZNSs (NH4 + -saturated, K + -saturated and dual-purpose NH4 + -K + saturated CLI) were produced, assessed, and compared with commercial N and K fertilizers (CFs) on corn growth in a greenhouse. The results indicated that CLI can potentially adsorb both NH4 + and K + to the maximum values of 25.00 mg-NH4 + g −1 and 47.61 mg-K g −1, respectively, and chemisorptions mainly followed the process of adsorption. Saturation of zeolite by NH4 + and K + occurred after 10 and 15 d which lead to ZNSs with 2% and 5% of N and K, respectively. NH4 + -K + saturated CLI contained 1% N and 1% K. The greenhouse experiment showed no significant difference between ZNSs and CFs on plant growth. However, the application of both N and K in the form of zeolitic sources significantly increased the uptake of N by the plant. The highest uptake of K (2.05 g pot −1 ) occurred in plants supplied with both natural zeolite and CFs. The present results may benefit the future utilization of ZNSs in environmental friendly farming practices.